Four species of Mazocraeoides Price, 1936 (Monogenea: Mazocraeidae), including two new species from clupeiform fishes off Visakhapatnam coast, Bay of Bengal - Sailaja, Bade; Shameem, Ummey; Madhavi, Rokkam (Zootaxa, 2019)
Four species of Mazocraeoides Price, 1936 including two new species are recorded from clupeiform fishes collected from Visakhapatnam Coast, Bay of Bengal: M. rotundus n. sp. from Ilisha filigera, M. fusiformes n. sp. from Stolephorus indicus, M. prashadi Chauhan, 1950 from Sardinella longiceps and M. dussumieri Mamaev, 1975 from Dussumieria hasselti. Mazocraeoides rotundus n. sp. is differentiated from the previously described species of Mazocraeoides by possessing the following combination of characters: the small pot-like body, the distribution of clamps in the posterior half of body and the genital complex consisting of five pairs of hooks arranged in two vertical rows. It differs from M. prashadi in the body shape and the much smaller size of the genital complex. Mazocraeoides fusiformes n. sp. differs from all the other species of the genus in the distribution of the clamps embracing only the posterior part of the testis and the genital complex consisting of one pair of needle-like lateral hooks and five pairs of median hooks. Mazocraeoides prashadi is redescribed to fill the gaps existing in the earlier description. Mazocraeoides dussumieri recorded earlier from South China Sea is reported for the first time from the Bay of Bengal. The validity of various species of Mazocraeoides is discussed and a key for the separation of valid species is provided. A host-parasite list is presented which gives details of the hosts, the geographic distribution and the validity status for each species. A partial 28S rDNA sequence was generated for M. dussumieri and deposited in GenBank.